Report on industrial attachment with Gemplus Technologies Asia Pte Ltd - Kusmanto, Daniel. (2008)
This report serves to describe the structure of two tools, which has been developed during the attachment period. The GemTest tool consists of Input Interface, compiler, and Test Generator.